2018
DOI: 10.1177/1753944718773690
|View full text |Cite
|
Sign up to set email alerts
|

Anandamide and endocannabinoid system: an attractive therapeutic approach for cardiovascular disease

Abstract: Cardiovascular disease is currently not adequately managed and has become one of the main causes of morbidity and mortality worldwide. Current therapies are inadequate in terms of preventing its progression. There are several limitations, such as poor oral bioavailability, side effects, low adherence to treatment, and high dosage frequency of formulations due to the short half-life of the active ingredients used, among others. This review aims to highlight the most relevant aspects of the relationship between … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
14
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 71 publications
0
14
0
Order By: Relevance
“…FAAH is a membrane-associated enzyme that is responsible for the degradation of endocannabinoids [ 12 ]. Therefore, the endocannabinoid system is an attractive therapeutic target for the treatment of hypertension and other cardiovascular diseases [ 9 , 13 ]. Given that AEA levels have been shown to regulate blood pressure [ 13 ], FAAH inhibitors are thought to be potential antihypertensive agents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…FAAH is a membrane-associated enzyme that is responsible for the degradation of endocannabinoids [ 12 ]. Therefore, the endocannabinoid system is an attractive therapeutic target for the treatment of hypertension and other cardiovascular diseases [ 9 , 13 ]. Given that AEA levels have been shown to regulate blood pressure [ 13 ], FAAH inhibitors are thought to be potential antihypertensive agents.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the endocannabinoid system is an attractive therapeutic target for the treatment of hypertension and other cardiovascular diseases [ 9 , 13 ]. Given that AEA levels have been shown to regulate blood pressure [ 13 ], FAAH inhibitors are thought to be potential antihypertensive agents. Previous studies in SHRs demonstrated that acute administration of the FAAH inhibitors URB597 [ 14 ] and AM3506 [ 15 ] results in a normalization of blood pressure and a decrease in cardiac contractility.…”
Section: Introductionmentioning
confidence: 99%
“…It has been demonstrated that as the ligand for the cannabinoid type 1 (CB1) and 2 (CB2) receptors, anandamide (AEA) exerts neuroprotective effects by inhibiting oxidative stress and free radical formation ( 8 ). Additionally, cannabinoids and activating cannabinoid receptors induce autophagy in cardiovascular disease ( 9 - 11 ).…”
Section: Introductionmentioning
confidence: 99%
“…For example, they decrease blood pressure (BP) and heart rate in humans, as well as in experimental animals, reduce tissue damage, delay the progression of the lesion, reduce the likelihood of presenting arrhythmias due to acute myocardial infarction, 4,5 and delay the development of atherosclerosis. [6][7][8] On the other hand, it has been shown that activation of CB1 receptors by anandamide produced by macrophages 9 or 2-AG by platelets 10 significantly contributes to the hypotension that occurs in different types of shock. 8,11 However, the mechanisms by which eCBs produce these physiological effects are not yet elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…[6][7][8] On the other hand, it has been shown that activation of CB1 receptors by anandamide produced by macrophages 9 or 2-AG by platelets 10 significantly contributes to the hypotension that occurs in different types of shock. 8,11 However, the mechanisms by which eCBs produce these physiological effects are not yet elucidated. 12 Oleamide, an amide derived from oleic acid, is considered an eCB that is naturally produced in some animals.…”
Section: Introductionmentioning
confidence: 99%